An organic-inorganic composite dense integrated diaphragm, a preparation method and application thereof

CN122968595APending Publication Date: 2026-10-23SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611154822.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

(1)热稳定性差

Benefits of technology

本发明提供的有机-无机复合致密一体化隔膜将多孔基膜、无机固态电解质和聚离子液体电解质改性材料三者进行复合,借由聚离子液体优异的耐高温性和阻燃性隔断电池热失控下的串扰反应,提高安全性,并利用聚离子液体和无机固态电解质之间的兼容性在电解质体相中提供了复合的快离子传输网络,并拓宽了该一体化隔膜的电化学稳定窗口;此外,二者搭配形成的复合材料高度的致密性和耐溶解/溶胀性还能抑制硫基电池中的穿梭效应,并阻隔正极溶出的过渡金属迁移至负极,缓解自放电以及活性物质的损失,提高电池的循环稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122968595A_ABST
    Figure CN122968595A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of diaphragms, and relates to an organic-inorganic composite dense integrated diaphragm as well as a preparation method and application thereof. The organic-inorganic composite dense integrated diaphragm comprises a porous base film, an inorganic solid-state electrolyte and a polyionic liquid electrolyte modification material. The inorganic solid-state electrolyte is distributed in at least part of the pores of the porous base film. The polyionic liquid electrolyte modification material is distributed on the surface of the porous base film and fills at least part of the pores of the porous base film. The polyionic liquid electrolyte modification material is formed by polymerization of a precursor solution comprising a polyionic liquid monomer, a multi-fluorine crosslinking agent and an initiator. Through the above structure and material collocation, the obtained dense integrated diaphragm can simultaneously meet multiple requirements of high ionic conductivity, excellent dissolution / swelling resistance, good mechanical strength, high safety and effective inhibition of the sulfur-based battery shuttle effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of membrane technology, and relates to an organic-inorganic composite dense integrated membrane, its preparation method and application. Background Technology

[0002] With the increasing prominence of the global energy crisis and environmental problems, electrochemical energy storage technologies, represented by lithium-ion batteries, have developed rapidly. In recent years, in order to further meet the urgent needs of electric vehicles, large-scale energy storage power stations, and high-end portable electronic devices for driving range and energy density, the development of new rechargeable battery systems with ultra-high energy density has become a research hotspot. Among them, lithium-sulfur batteries (theoretical energy density of 2600 Wh / kg) and lithium metal batteries (using lithium metal anodes, theoretical specific capacity of 3860 mAh / g) have attracted much attention due to their extremely high theoretical advantages. However, the commercialization process of these new battery systems still faces key challenges such as poor cycle stability and significant safety hazards.

[0003] In lithium-ion battery structures, the separator, as a key component that isolates the positive and negative electrodes, prevents electron conduction but allows ion migration, directly determines the battery's cycle life, rate performance, and safety characteristics. Currently, commercially available lithium-ion batteries generally use polyethylene (PE) or polypropylene (PP) microporous separators. Although these polyolefin separators have advantages in cost and processing performance, they have revealed many insurmountable shortcomings when dealing with next-generation high-energy-density batteries: (1) Poor thermal stability. Polyolefin materials have low melting points (PE about 135°C, PP about 165°C). When the battery overheats or thermal runaway occurs, the separator is very prone to thermal shrinkage or melting, which can lead to direct contact between the positive and negative electrodes, causing an internal short circuit and inducing a fire and explosion. In addition, traditional organic liquid electrolytes usually use carbonate solvents with low flash points, which are very easy to burn under high temperature conditions. They cannot block the chain reaction in the thermal runaway process and may even accelerate the runaway process.

[0004] (2) Insufficient mechanical strength. Faced with the volume expansion and lithium dendrite growth generated by the lithium metal anode during cycling, the polyolefin separator with limited mechanical strength is difficult to provide an effective physical barrier and is easily pierced by dendrites, causing battery failure. At the same time, the polyolefin material has low surface energy and poor wettability to electrolyte, resulting in limited ionic conductivity. Moreover, at room temperature, ion transport mainly depends on the movement of polymer chain segments, and the conductivity is usually less than 1 mS / cm, which limits the rate performance of the battery.

[0005] (3) Lack of ability to suppress shuttle effect. In lithium-sulfur batteries, intermediate lithium polysulfides (LiPSs) are readily soluble in ether electrolytes and migrate back and forth between the positive and negative electrodes under the drive of concentration gradient (i.e., "shuttle effect"), resulting in irreversible loss of active material and corrosion of the negative electrode. Traditional polyolefin membranes have large pore size and no chemical adsorption sites, and cannot effectively block the shuttle of polysulfides.

[0006] (4) Limitations of polymer electrolytes themselves. The transport of lithium ions in polymer frameworks is mostly concentrated in amorphous regions above their glass transition temperature. The room temperature ionic conductivity is low, and the polar groups on polymer segments are prone to oxidation at low potentials, reducing the electrochemical stability window of polymer electrolytes. In addition, most polymer electrolytes are prone to swelling or even dissolution when immersed in highly polar organic electrolytes for a long time, leading to structural collapse.

[0007] (5) Interface challenges of inorganic solid electrolytes. Although oxide / halide / sulfide solid electrolytes have high ionic conductivity and wide electrochemical window, they are extremely sensitive to air (especially water vapor), and are brittle and lack toughness, making it difficult to maintain good solid-solid contact with electrode materials. This results in excessively high interfacial impedance, which limits their application under low stacking pressure (<1MPa).

[0008] In summary, most of the membrane materials or electrolyte systems in the existing technology have defects such as poor high-temperature stability, low mechanical strength, narrow electrochemical stability window, and insufficient room-temperature ionic conductivity.

[0009] Therefore, in order to address the aforementioned technical deficiencies, there is an urgent need to develop an organic-inorganic composite dense integrated separator that can simultaneously meet multiple requirements such as high ionic conductivity, excellent resistance to dissolution / swelling, good mechanical strength, and effective suppression of the shuttle effect in sulfur-based batteries. Summary of the Invention

[0010] To address the shortcomings of existing technologies, the present invention aims to provide an organic-inorganic composite dense integrated separator, its preparation method, and its application. The organic-inorganic composite dense integrated separator can simultaneously meet multiple requirements such as high ionic conductivity, excellent resistance to dissolution / swelling, good mechanical strength, and effective suppression of the shuttle effect in sulfur-based batteries.

[0011] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides an organic-inorganic composite dense integrated membrane, wherein the organic-inorganic composite dense integrated membrane comprises a porous base membrane, an inorganic solid electrolyte, and a polyionic liquid electrolyte modified material; The inorganic solid electrolyte is at least distributed in a portion of the pores of the porous base membrane; The polyionic liquid electrolyte modifier is distributed on the surface of the porous base membrane and fills at least a portion of the pores of the porous base membrane; The polyionic liquid electrolyte modified material is formed by precursor solution polymerization comprising polyionic liquid monomers, polyfluorinated crosslinking agents and initiators.

[0012] On one hand, the organic-inorganic composite dense integrated diaphragm provided by the present invention uses a porous base membrane as a supporting framework. First, an inorganic solid electrolyte is uniformly dispersed in at least a portion of the pores of the porous base membrane by impregnation and ultrasound. Then, a polyionic liquid electrolyte modifier is introduced by in-situ polymerization, and the polyionic liquid electrolyte modifier is distributed on the surface of the porous base membrane and fills at least a portion of the pores of the porous base membrane. The pores of the porous base membrane are first filled with inorganic solid electrolyte, and then the pores of the porous base membrane are filled with polyionic liquid electrolyte modifier, and the surface of the porous diaphragm is coated, making the resulting diaphragm structurally very dense.

[0013] On the other hand, the present invention further specifies that the modified polyionic liquid electrolyte is formed by precursor solution polymerization comprising polyionic liquid monomers, polyfluorinated crosslinking agents, and initiators. Firstly, the polyionic liquid network formed by the polyionic liquid monomers can coat inorganic solid electrolytes with high water / oxygen sensitivity, providing them with a more user-friendly working environment while ensuring efficient ion transport channels in the composite material formed by the polyionic liquid and inorganic solid electrolyte. Simultaneously, the combination of the inorganic solid electrolyte with intrinsically high oxidation stability and the polyionic liquid electrolyte can broaden the electrochemical stability window of the integrated polymer membrane to a certain extent. Secondly, thanks to the structural design of the polyionic liquid monomers, they exhibit excellent resistance to dissolution / swelling after copolymerization with polyfluorinated crosslinking agents under photo / thermal initiation conditions, resulting in a dense, integrated membrane. Even after prolonged immersion in highly polar organic solvents, it does not suffer significant damage, thus protecting its internal high-efficiency ion channels. Simultaneously, the high density of this organic-inorganic composite dense integrated separator is guaranteed, maintaining good barrier properties against small molecules. Finally, due to the high stability of the functional groups on the polymer segments, the solubility of lithium polysulfide / sodium polysulfide is very low, suppressing their shuttle effect in sulfur-based batteries and significantly reducing self-discharge and the consumption of limited active materials. Furthermore, without sacrificing the toughness of the porous base membrane as a framework, its mechanical properties are enhanced, facilitating stability during operation. The excellent high-temperature resistance and flame retardancy of the polyionic liquid also help prevent crosstalk reactions under thermal runaway, improving the separator's safety.

[0014] In summary, the organic-inorganic composite dense integrated separator provided by this invention can simultaneously meet multiple requirements such as high ionic conductivity, excellent resistance to dissolution / swelling, good mechanical strength, high safety, and effective suppression of shuttle effect in sulfur-based batteries.

[0015] Preferably, the inorganic solid electrolyte in the organic-inorganic composite dense integrated membrane has a mass percentage content of 30-90%, such as 30%, 40%, 50%, 60%, 70%, 80% or 90%, and more preferably 60-85%.

[0016] Preferably, the inorganic solid electrolyte includes any one or a combination of at least two of oxide solid electrolytes, halide solid electrolytes, or sulfide solid electrolytes.

[0017] Preferably, the inorganic solid electrolyte comprises Li7La3Zr2O 12 Li 6.4 La3Zr 1.4 Ta 0.6 O 12 Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li3InCl6, Li 2.6 In 0.8 Ta 0.2 Cl6, Li3YCl6, Li 10 GeP2S 12 Li7P3S 7.5 O 3.5 Or any one or a combination of at least two of Li6PS5Cl.

[0018] Preferably, the porosity of the porous base membrane is 10-90%, such as 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% or 90%, and more preferably 30-60%.

[0019] In this invention, the porosity of the porous base membrane is tested according to the method provided in GB / T 36363-2018 "Polyolefin separators for lithium-ion batteries".

[0020] Preferably, the average pore size of the porous base film is 0.01~1 μm, such as 0.01 μm, 0.05 μm, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1 μm, and more preferably 0.1~0.5 μm.

[0021] In this invention, the average pore size of the porous base membrane is obtained by testing according to the method provided in GB / T 32361-2015 "Separation Membrane Pore Size Test Method Bubble Point and Average Flow Rate Method".

[0022] In this invention, the porous base membrane has a three-dimensional network structure. This invention does not have specific requirements regarding the type of porous base membrane provided, as long as its porosity and average pore size meet the limitations of this invention. Preferably, the porous base membrane can be a pure organic porous base membrane, a pure inorganic porous base membrane, or an organic / inorganic composite porous membrane. The organic porous base membrane is further preferably any one of a polyolefin porous membrane, a polyvinylidene fluoride porous membrane, a polyimide porous membrane, a polyacrylonitrile porous membrane, a polysulfone porous membrane, or a polyacetate cellulose porous membrane. The inorganic porous base membrane is further preferably made of alumina and / or silica.

[0023] Preferably, the mass percentage of polyionic liquid monomer in the precursor solution is 10-90%, such as 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80% or 90%, and more preferably 15-60%.

[0024] Preferably, the polyionic liquid monomer has the structure shown in Formula I: Formula I; In Equation I, m and n are each independent integers from 0 to 10 (e.g., 1, 2, 3, 4, 5, 6, 7, 8, or 9, etc.), and R F Fluorinated alkyl groups selected from C1 to C10 (e.g., C1, C2, C4, C6, C8, or C10, etc.) with straight or branched chains.

[0025] Preferably, the R F It is selected from any one of trifluoromethyl, pentafluoroethyl, perfluorobutyl, or perfluorohexyl.

[0026] Preferably, the polyionic liquid monomer is prepared by the following method, which includes the following steps: (A1) Compound 1 and compound 2 are reacted to obtain compound 3, and the reaction formula is as follows: ; (A2) Compound 3 and compound 4 are reacted to obtain compound 5, and the reaction formula is as follows: ; (A3) Compound 5 and lithium bis(trifluoromethanesulfonyl)imide were reacted to obtain the polyionic liquid monomer, and the reaction formula is as follows: ; Where X and Y are both halogens (e.g., Cl, Br, etc.), m and n are each independent integers from 0 to 10 (e.g., 1, 2, 3, 4, 5, 6, 7, 8, or 9, etc.), and R F It is a straight-chain or branched fluorinated alkyl group of C1 to C20 (e.g., C1, C2, C4, C6, C8, C10, C12, C14, C16, C18 or C20, etc.).

[0027] Preferably, the molar ratio of compound 1 to compound 2 in step (A1) is 1:1.

[0028] Preferably, the temperature of the reaction in step (A1) is 0~50℃, for example 0℃, 10℃, 20℃, 30℃, 40℃ or 50℃, and more preferably 0~25℃.

[0029] Preferably, the reaction time in step (A1) is 1 to 72 h, such as 1 h, 5 h, 10 h, 20 h, 30 h, 40 h, 50 h, 60 h or 70 h, and more preferably 10 to 20 h.

[0030] Preferably, the molar ratio of compound 3 and compound 4 in step (A2) is 1:1.

[0031] Preferably, the reaction temperature in step (A2) is 50~100℃, such as 50℃, 60℃, 70℃, 80℃, 90℃ or 100℃, and more preferably 75~95℃.

[0032] Preferably, the reaction time in step (A2) is 1 to 72 h, such as 1 h, 5 h, 10 h, 20 h, 30 h, 40 h, 50 h, 60 h or 70 h, and more preferably 20 to 30 h.

[0033] Preferably, the molar ratio of compound 5 and lithium bis(trifluoromethanesulfonyl)imide in step (A3) is 1:3.

[0034] Preferably, the reaction temperature in step (A3) is 20~45°C, for example 20°C, 24°C, 28°C, 32°C, 35°C, 40°C or 42°C, and more preferably 25~30°C.

[0035] Preferably, the reaction time in step (A3) is 1 to 72 hours, such as 1 hour, 5 hours, 10 hours, 15 hours, 20 hours, 25 hours, 30 hours, 35 hours, 40 hours, 45 hours, 50 hours, 60 hours or 70 hours, and more preferably 8 to 24 hours.

[0036] Preferably, the mass percentage of the polyfluorinated crosslinking agent in the precursor solution is 1-30%, such as 1%, 5%, 10%, 15%, 20%, 25% or 30%, and more preferably 1-10%.

[0037] Preferably, the polyfluorinated crosslinking agent has the structure shown in Formula II: Formula II; In Formula II, a is an integer from 1 to 5 (e.g., 2, 3 or 4), and R1 is selected from any one of ester, ether, carbonyl or alkylene groups.

[0038] Preferably, a is an integer from 2 to 4.

[0039] Preferably, the polyfluorinated crosslinking agent comprises any one or a combination of at least two of 1,4-divinylperfluorobutane, 1,6-divinylperfluorohexane, or 2,2,3,3,4,4,5,5-octafluorohexane-1,6-dimethyldiacrylate.

[0040] Preferably, the initiator in the precursor solution has a mass percentage content of 0.01 to 2%, such as 0.01%, 0.02%, 0.05%, 0.1%, 0.2%, 0.5%, 1%, 1.5%, or 2%, and more preferably 0.05 to 1%.

[0041] Preferably, the initiator includes a photoinitiator and / or a thermal initiator.

[0042] Preferably, the photoinitiator comprises any one or a combination of at least two of 1-hydroxycyclohexylphenyl ketone (HCPK), phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (TPO), or 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP).

[0043] Preferably, the thermal initiator includes any one or a combination of at least two of azobisisobutyronitrile (AIBN), benzoyl peroxide (BPO), or potassium persulfate (KPS).

[0044] Preferably, the precursor solution further includes a lithium salt.

[0045] Preferably, the lithium salt content in the precursor solution is ≤70% by mass, such as 10%, 20%, 30%, 40%, 50%, 60% or 70%, and more preferably ≤30%.

[0046] Preferably, the lithium salt comprises any one or a combination of at least two of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium hexafluorophosphate (LiPF6), lithium difluorooxalate borate (LiDFOB), lithium bis(oxalate borate) (LiBOB), or lithium tetrafluoroborate (LiBF4).

[0047] In a second aspect, the present invention provides a method for preparing an organic-inorganic composite dense integrated separator as described in the first aspect, the method comprising the following steps: (1) The porous base membrane is immersed in a solution containing inorganic solid electrolyte and subjected to ultrasonic treatment, and then dried to obtain a porous base membrane loaded with inorganic solid electrolyte. A precursor solution is obtained by mixing a polyionic liquid monomer, a polyfluorinated crosslinking agent, an initiator, and optionally a lithium salt. (2) The precursor solution obtained in step (1) is used to impregnate the porous base membrane loaded with inorganic solid electrolyte obtained in step (1), and after polymerization, the organic-inorganic composite dense integrated membrane is obtained.

[0048] Preferably, the solution containing the inorganic solid electrolyte in step (1) is obtained by dispersing the inorganic solid electrolyte in an organic solvent.

[0049] Preferably, the organic solvent includes any one or a combination of at least two of anhydrous toluene, anhydrous xylene, or anhydrous n-heptane.

[0050] Preferably, the ultrasonic treatment time in step (1) is 0.1 to 5 h, such as 0.1 h, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h or 5 h, and more preferably 0.5 to 2 h.

[0051] Preferably, the polymerization in step (2) is photoinitiated polymerization and / or thermally initiated polymerization, and more preferably photoinitiated polymerization.

[0052] Preferably, the temperature for thermally initiated polymerization is 60~80℃, such as 60℃, 62℃, 64℃, 66℃, 68℃, 70℃, 72℃, 74℃, 76℃, 78℃ or 80℃.

[0053] Preferably, the thermally initiated polymerization time is 4 to 25 hours, such as 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 18 hours, 20 hours, 22 hours, or 24 hours.

[0054] Preferably, the photoinitiated polymerization is UV photoinitiated polymerization, and the time is 2 to 10 minutes, such as 2 minutes, 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes or 10 minutes.

[0055] Thirdly, the present invention provides a lithium metal battery, the lithium metal battery comprising an organic-inorganic composite dense integrated separator as described in the first aspect.

[0056] For example, the manufacturing process of the lithium metal battery is as follows: placing a 12 mm diameter LiNi electrode in a CR2032 stainless steel positive electrode shell. 0.8 Co 0.1 Mn 0.1 O2 positive electrode sheet, 25 μL of liquid electrolyte (lithium-ion secondary electrolyte LB-141) is dropped onto the positive electrode sheet, then the organic-inorganic composite dense integrated separator as described in the first aspect is placed in the middle of the battery case; then another 25 μL of liquid electrolyte (lithium-ion secondary electrolyte LB-141) is dropped onto the separator, and then the lithium metal negative electrode, gasket, spring sheet and negative electrode shell are assembled in sequence, and finally it is packaged using a button cell battery packaging machine, with the pressure controlled below 500 MPa, to obtain the lithium metal battery.

[0057] Fourthly, the present invention provides a lithium-sulfur battery, the lithium-sulfur battery comprising an organic-inorganic composite dense integrated separator as described in the first aspect.

[0058] For example, the manufacturing process of the lithium-sulfur battery is as follows: a sulfur / carbon nanotube composite material with a diameter of 12 mm loaded on an aluminum foil current collector is placed in a CR2032 stainless steel positive electrode shell as a positive electrode sheet. 25 μL of liquid electrolyte (lithium-ion secondary electrolyte LB-141) is dropped onto the positive electrode sheet. Then, the organic-inorganic composite dense integrated separator prepared in Example 1 is placed in the middle of the battery shell. Another 25 μL of liquid electrolyte (lithium-ion secondary electrolyte LB-141) is dropped onto the separator. Then, the lithium metal negative electrode sheet, gasket, spring sheet and negative electrode shell are assembled in sequence. Finally, the battery is packaged using a button cell battery packaging machine, and the pressure is controlled below 500 MPa to obtain the lithium-sulfur battery.

[0059] In this invention, the electrolyte used in the lithium metal electrode and lithium-sulfur battery includes ester electrolytes and / or ether electrolytes containing 1,3-dioxolane (DOL).

[0060] Compared with the prior art, the present invention has the following beneficial effects: The organic-inorganic composite dense integrated separator provided by this invention combines a porous base membrane, an inorganic solid electrolyte, and a polyionic liquid electrolyte modification material. The excellent high-temperature resistance and flame retardancy of the polyionic liquid isolate crosstalk reactions under battery thermal runaway, improving safety. Furthermore, the compatibility between the polyionic liquid and the inorganic solid electrolyte provides a composite fast ion transport network in the electrolyte bulk phase, broadening the electrochemical stability window of the integrated separator. In addition, the high density and resistance to dissolution / swelling of the composite material can suppress the shuttle effect in sulfur-based batteries and prevent the migration of transition metals dissolved from the positive electrode to the negative electrode, mitigating self-discharge and loss of active materials, thus improving the battery's cycle stability. Attached Figure Description

[0061] Figure 1 The NMR spectrum of the polyionic liquid monomer provided in Example 1 is shown. Figure 2 This is a cross-sectional scanning electron microscope image of the organic-inorganic composite dense integrated diaphragm provided in Example 1. Detailed Implementation

[0062] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0063] Preparation Example 1 A polyionic liquid monomer, the structural formula of which is shown below: ; The preparation method of the polyionic liquid monomer provided in this example includes the following steps: (1) Compound 1 and compound 2, with a molar ratio of 1:1, were reacted at 20°C for 15 h to obtain compound 3, as shown in the following reaction formula: ; (2) Compound 3 and compound 4, with a molar ratio of 1:1, were reacted at 80 °C for 25 h to obtain compound 5, as shown in the following reaction formula: ; (3) Compound 5 and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in a molar ratio of 1:3 were reacted at 30°C for 20 h to obtain the polyionic liquid monomer; .

[0064] Structural characterization: The polyionic liquid monomer obtained in Preparation Example 1 was tested using nuclear magnetic resonance (NMR) with DMSO as the solvent and a test frequency of 100 MHz. The test results are as follows: Figure 1As shown; from Figure 1 It can be seen that this preparation example 1 proves that a polyionic liquid monomer with the above-mentioned specific structure was successfully synthesized.

[0065] Preparation Example 2 A polyionic liquid monomer, the structural formula of which is shown below: ; The preparation method of the polyionic liquid monomer provided in this preparation example includes the following steps: (1) reacting compound 1 and compound 2 in a molar ratio of 1:1 at 15°C for 20 h to obtain compound 3, the reaction formula is as follows: ; (2) Compound 3 and compound 4, with a molar ratio of 1:1, were reacted at 90℃ for 20 h to obtain compound 5, as shown in the following reaction formula: ; (3) Compound 5 and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) in a molar ratio of 1:3 were reacted at 25°C for 12 h to obtain the polyionic liquid monomer; .

[0066] Example 1 An organic-inorganic composite dense integrated membrane, comprising a porous base membrane, an inorganic solid electrolyte, and a polyionic liquid electrolyte modified material; The inorganic solid electrolyte is at least distributed in a portion of the pores of the porous base membrane; The polyionic liquid electrolyte modifying material is distributed on the surface of the porous base membrane and fills at least a portion of the pores of the porous base membrane; The polyionic liquid electrolyte modified material is formed by precursor solution polymerization comprising polyionic liquid monomers, polyfluorinated crosslinking agents and initiators; The porous base membrane is a polyethylene base membrane with a thickness of 15 μm, a diameter of 19 mm, a porosity of 50%, and an average pore size of 0.3 μm. The inorganic solid electrolyte is Li3InCl6, and its mass percentage in the organic-inorganic composite dense integrated membrane is 70%. The precursor solution comprises 70% by mass of a polyionic liquid monomer (Preparation Example 1), 10% by mass of 1,4-divinylperfluorobutane, 19% by mass of LiFSI, and 1% by mass of HCPK. The method for preparing the organic-inorganic composite dense integrated separator provided in Example 1 includes the following steps: (1) Add Li3InCl6 particles to anhydrous n-heptane and mechanically stir for 30 min, then ultrasonically treat for 30 min to obtain a slurry. Immerse the polyethylene base membrane in the obtained slurry and ultrasonically treat for 2 h to fully wet the internal pores of the base membrane. Then transfer it to a vacuum oven and keep it at 80°C for 6 h to complete solvent evaporation and obtain a porous base membrane loaded with Li3InCl6. The polyionic liquid monomer provided in Example 1 was extracted using a pipette and placed in a pre-washed, dried volumetric flask containing a magnetic ball. 1,4-Divinylperfluorobutane, LiFSI and HCPK were added. The mixture was stirred continuously for 30 min under completely dark conditions, and then mixed for 30 min using a high-speed stirrer at 2000 rpm to obtain the precursor solution. (2) Using a pipette, take 60 μL of the precursor solution obtained in step (1) into a polytetrafluoroethylene template with a diameter of 19 mm, cover it with a polyethylene film loaded with Li3InCl6 with a diameter of 19 mm, and after it is completely wetted by the precursor solution, add the remaining precursor solution to the upper layer of the polyethylene film loaded with Li3InCl6. After waiting for 2 min, use a UV lamp with a wavelength of 365 nm to irradiate for 2 min to fully solidify it, and obtain the organic-inorganic composite dense integrated membrane.

[0067] Example 2 An organic-inorganic composite dense integrated membrane differs from Example 1 only in that the polyionic liquid monomer provided in Preparation Example 2 is used instead of the polyionic liquid monomer provided in Preparation Example 1. All other substances, amounts, and preparation methods are the same as in Example 1.

[0068] Example 3 An organic-inorganic composite dense integrated membrane, which differs from Example 1 only in that it uses Li 10 GeP2S 12 The Li3InCl6 was replaced, and all other substances, amounts, and preparation methods were the same as in Example 1.

[0069] Example 4 An organic-inorganic composite dense integrated membrane differs from Example 1 only in that 1,6-divinylperfluorohexane is used instead of 1,4-divinylperfluorobutane, while the other substances, amounts, and preparation methods are the same as in Example 1.

[0070] Example 5 An organic-inorganic composite dense integrated membrane differs from Example 1 only in that 2,2,3,3,4,4,5,5-octafluorohexane-1,6-dimethyldiacrylate is used instead of 1,4-divinylperfluorobutane. All other substances, amounts, and preparation methods are the same as in Example 1.

[0071] Example 6 An organic-inorganic composite dense integrated separator differs from Example 1 as follows: The precursor solution comprises 20% by mass of a polyionic liquid monomer (Preparation Example 1), 30% by mass of 1,4-divinylperfluorobutane, 49% by mass of LiFSI, and 1% by mass of HCPK. The other substances, dosages, and preparation methods are the same as in Example 1.

[0072] Example 7 An organic-inorganic composite dense integrated separator differs from Example 1 as follows: The precursor solution comprises 80% by mass of a polyionic liquid monomer (Preparation Example 1), 5% by mass of 1,4-divinylperfluorobutane, 14.95% by mass of LiFSI, and 0.05% by mass of HCPK. The other substances, dosages, and preparation methods are the same as in Example 1.

[0073] Example 8 An organic-inorganic composite dense integrated membrane differs from Example 1 only in that AIBN is used instead of HCPK, and the polymerization method in step (2) of the preparation method is changed to placing it in a high-temperature oven at 70°C for 20 h. Other substances, amounts and steps are the same as in Example 1.

[0074] Comparative Example 1 A diaphragm differs from Example 1 only in that 1,4-divinylperfluorobutane is not added, the amount of polyionic liquid monomer (Preparation Example 1) is 70%, the amount of LiFSI is 29%, and the amount of HCPK is 1%. The other substances, dosages, and procedures are the same as in Example 1.

[0075] Comparative Example 2 A diaphragm, differing from Example 1 only in that Li3InCl6 was not added, the amount of polyionic liquid monomer (Preparation Example 1) was 60%, the amount of 1,4-divinylperfluorobutane was 15%, the amount of LiFSI was 24%, and the amount of HCPK was 1%. The other substances, dosages, and procedures are the same as in Example 1.

[0076] Comparative Example 3 A membrane, which differs from Example 1 only in that no polyionic liquid monomer is added (Preparation Example 1), the amount of 1,4-divinylperfluorobutane is 30%, the amount of LiFSI is 69%, and the amount of HCPK is 1%; The other substances, dosages, and procedures are the same as in Example 1.

[0077] Performance testing of the diaphragm: (1) Appearance: The cross-section of the organic-inorganic composite dense integrated separator provided in Example 1 was tested using a scanning electron microscope (SEM, Hitachi S-4800). The cross-sectional scanning electron microscope image of the organic-inorganic composite dense integrated separator provided in Example 1 is shown below. Figure 2 As shown; from Figure 2 It can be seen that in the organic-inorganic composite dense integrated membrane provided in Example 1, the high-porosity base membrane is fully permeated and filled by inorganic solid electrolyte and polyionic liquid electrolyte modified materials, forming a dense integrated composite membrane without internal through pores. This enables it to have both high mechanical strength and high ionic conductivity, and can effectively suppress the shuttle effect of polysulfides.

[0078] (2) Thermal stability: Thermogravimetric analysis (TGA) was used to measure the weight change of the diaphragm at high temperature, thereby analyzing its thermal stability and obtaining the thermal decomposition temperature; the test machine model was TGA / DTA 6300, about 10 mg of sample was weighed, the test temperature range was 30~500℃, and the heating rate was 10℃ min. -1 The flow rate of nitrogen gas is approximately 15 mL / min. -1 .

[0079] (3) Ionic conductivity: A stainless steel symmetrical cell (SS|separator|SS) was assembled in a glove box. After the cell was assembled, it was transferred to an electrochemical workstation (model VMP-300) for EIS testing to obtain its bulk impedance Rb. The test frequency was 7MHz to 500MHz and the voltage amplitude was 10mV. The specific value of its ionic conductivity σ can then be obtained from formula 1: σ=L / (R b ×S) Formula 1; Where L is the electrolyte thickness and S is the area of ​​the electrolyte membrane.

[0080] (4) Oxidation potential: After assembling an SS|membrane|Li battery in a glove box, LSV test was performed on it using an electrochemical workstation (model VMP-300). The voltage scan range was from open circuit voltage to 6.0 V, and the scan rate was 0.1 mV / s. The final oxidation potential is the potential corresponding to the appearance of a significant oxidation current response.

[0081] (5) Cycling performance of lithium metal battery: After assembling an NCM811|separator|Li battery in a glove box, it was transferred to Neware's constant temperature (30℃) battery test cabinet and left for 6 hours. Then, the battery was activated for five weeks at 0.1C with a small current using the constant current charge-discharge test method. After cycling the battery for 200 cycles at 0.5C, the ratio of the battery discharge specific capacity to the initial value was tested to reflect its cycle performance.

[0082] (6) Cycling performance of lithium-sulfur battery: After assembling an S@GT300|separator|Li battery in a glove box, it was transferred to Neware's constant temperature (30℃) battery test cabinet and left for 6 hours. Then, the battery was activated for five weeks at 0.1C with a small current using the constant current charge-discharge test method. After cycling the battery for 200 cycles at 0.5C, the ratio of the battery discharge specific capacity to the initial value was tested to reflect its cycle performance.

[0083] The diaphragms provided in Examples 1-8 and Comparative Examples 1-3 were tested according to the above test methods, and the test results are shown in Table 1: Table 1 According to the data in Table 1: The lithium metal batteries made from the organic-inorganic composite dense integrated separators provided in Examples 1-8 have an ionic conductivity of not less than 0.23 mS / cm. -1 The oxidation potential is not lower than 4.59 V, and after 200 cycles at 0.5C, the ratio of the battery's discharge specific capacity to its initial value is not lower than 80%. The membrane provided in Comparative Example 1 had insufficient resistance to dissolution / swelling due to the lack of polyfluorinated crosslinking agent; the membrane provided in Comparative Example 2 had low ionic conductivity due to the lack of inorganic solid electrolyte; and the membrane provided in Comparative Example 3 had poor thermal and mechanical stability due to the lack of polyionic liquid electrolyte. Therefore, the cycle stability of all three membranes decreased significantly.

[0084] In addition, the lithium-sulfur batteries made from the organic-inorganic composite dense integrated separators provided in Examples 1-8 also exhibit excellent cycle performance.

[0085] The above description is a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention fall within the scope of protection and disclosure of the present invention.

Claims

1. An organic-inorganic composite dense integrated separator, characterized in that, The organic-inorganic composite dense integrated membrane includes a porous base membrane, an inorganic solid electrolyte, and a polyionic liquid electrolyte modified material; The inorganic solid electrolyte is at least distributed in a portion of the pores of the porous base membrane; The polyionic liquid electrolyte modifier is distributed on the surface of the porous base membrane and fills at least a portion of the pores of the porous base membrane; The polyionic liquid electrolyte modified material is formed by polymerization of a precursor solution containing polyionic liquid monomers, polyfluorinated crosslinking agents and initiators.

2. The organic-inorganic composite dense integrated separator according to claim 1, characterized in that, The inorganic solid electrolyte in the organic-inorganic composite dense integrated diaphragm is 30-90% by mass, preferably 60-85%; Preferably, the inorganic solid electrolyte includes any one or a combination of at least two of oxide solid electrolytes, halide solid electrolytes, or sulfide solid electrolytes; Preferably, the inorganic solid electrolyte comprises Li7La3Zr2O 12 Li 6.4 La3Zr 1.4 Ta 0.6 O 12 Li 1.3 Al 0.3 Ti 1.7 (PO4)3, Li3InCl6, Li 2.6 In 0.8 Ta 0.2 Cl6, Li3YCl6, Li 10 GeP2S 12 Li7P3S 7.5 O 3.5 Or any one or a combination of at least two of Li6PS5Cl.

3. The organic-inorganic composite dense integrated separator according to claim 1, characterized in that, The porosity of the porous base membrane is 10-90%, preferably 30-60%; Preferably, the average pore size of the porous base membrane is 0.01~1 μm, and more preferably 0.1~0.5 μm.

4. The organic-inorganic composite dense integrated separator according to claim 1, characterized in that, The precursor solution contains 10-90% by mass of polyionic liquid monomer, preferably 15-60%. Preferably, the polyionic liquid monomer has the structure shown in Formula I: Equation I; In Equation I, m and n are each independent integers from 0 to 10, and R F Selected from C1~C10 straight-chain or branched fluorinated alkyl groups; Preferably, the R F It is selected from any one of trifluoromethyl, pentafluoroethyl, perfluorobutyl, or perfluorohexyl.

5. The organic-inorganic composite dense integrated separator according to claim 1, characterized in that, The mass percentage of the polyfluorinated crosslinking agent in the precursor solution is 1-30%, preferably 1-10%. Preferably, the polyfluorinated crosslinking agent has the structure shown in Formula II: Formula II; In Formula II, a is an integer from 1 to 5, and R1 is selected from any one of ester group, ether group, carbonyl group or alkylene group; Preferably, 'a' is an integer from 2 to 4; Preferably, the polyfluorinated crosslinking agent comprises any one or a combination of at least two of 1,4-divinylperfluorobutane, 1,6-divinylperfluorohexane, or 2,2,3,3,4,4,5,5-octafluorohexane-1,6-dimethyldiacrylate.

6. The organic-inorganic composite dense integrated separator according to claim 1, characterized in that, The initiator in the precursor solution has a mass percentage content of 0.01-2%, preferably 0.05-1%. Preferably, the initiator includes a photoinitiator and / or a thermal initiator; Preferably, the photoinitiator comprises any one or a combination of at least two of 1-hydroxycyclohexylphenyl ketone, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, or 2-hydroxy-2-methyl-1-phenyl-1-propanone; Preferably, the thermal initiator includes any one or a combination of at least two of azobisisobutyronitrile, benzoyl peroxide, or potassium persulfate; Preferably, the precursor solution further includes a lithium salt; Preferably, the lithium salt content in the precursor solution is ≤70% by mass, and more preferably ≤30%. Preferably, the lithium salt comprises any one or a combination of at least two of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium difluorooxalate borate, lithium bis(oxalate borate), or lithium tetrafluoroborate.

7. A method for preparing an organic-inorganic composite dense integrated separator as described in any one of claims 1 to 6, characterized in that, The preparation method includes the following steps: (1) The porous base membrane is immersed in a solution containing inorganic solid electrolyte and subjected to ultrasonic treatment, and then dried to obtain a porous base membrane loaded with inorganic solid electrolyte. A precursor solution is obtained by mixing a polyionic liquid monomer, a polyfluorinated crosslinking agent, an initiator, and optionally a lithium salt. (2) The precursor solution obtained in step (1) is used to impregnate and fill the gaps of the porous base membrane loaded with inorganic solid electrolyte obtained in step (1), and after polymerization, the organic-inorganic composite dense integrated membrane is obtained.

8. The preparation method according to claim 7, characterized in that, The solution containing the inorganic solid electrolyte in step (1) is obtained by dispersing the inorganic solid electrolyte in an organic solvent; Preferably, the organic solvent includes any one or a combination of at least two of anhydrous toluene, anhydrous xylene, or anhydrous n-heptane; Preferably, the ultrasonic treatment time in step (1) is 0.1~5 h, more preferably 0.5~2 h; Preferably, the polymerization in step (2) is photoinitiated polymerization and / or thermally initiated polymerization, and more preferably photoinitiated polymerization; Preferably, the temperature for thermally initiated polymerization is 60~80℃, and the time is 4~25 h; Preferably, the photoinitiated polymerization is UV photoinitiated polymerization, and the time is 2~10 min.

9. A lithium metal battery, characterized in that, The lithium metal battery includes the organic-inorganic composite dense integrated separator as described in any one of claims 1 to 6.

10. A lithium-sulfur battery, characterized in that, The lithium-sulfur battery includes the organic-inorganic composite dense integrated separator as described in any one of claims 1 to 6.